Computed tomography coronary angiography: Is radiation a concern for the gold standard test for anomalous coronary arteries? - Khaled Alfakih (JRSM Cardiovascular Disease, 2014)
Multi-detector computed tomography is now an established modality for the investigation of coronary artery disease.1,2^ 64-Slice multi-detector computed tomography is the standard requirement by the British society of cardiac imaging and can image the whole heart in four heart beats. The 320 slice multi-detector computed tomography can image the heart in one heart beat, but both technologies depend on B-blockers to slow the patient’s heart rate to 60 beats per minute to ensure excellent image quality and low radiation dose. The faster dual source multi-detector computed tomography is less dependent on B-blockers. The availability and ease of use of multi-detector computed tomography has meant that it is increasingly used in younger patients to rule out coronary artery disease or rule out anomalous coronary arteries. We consider the radiation associated with computed tomography coronary angiography and the available dose reduction techniques.